Sensing behavior of atomically thin-layered MoS2 transistors - Late, Dattatray J.; Huang, Yi-Kai; Liu, Bin; Acharya, Jagaran; Shirodkar, Sharmila N.; Luo, Jiajun; Yan, Aiming; Charles, Daniel; Waghmare, Umesh V.; Dravid, Vinayak P.; Rao, C. N. R. (ACS Nano, 2013)
Most of recent research on layered chalcogenides is understandably focused on single atomic layers. However, it is unclear if single-layer units are the most ideal structures for enhanced gas solid interactions. To probe this issue further, we have prepared large-area MoS2 sheets ranging from single to multiple layers on 300 nm SiO2/Si substrates using the micromechanical exfoliation method. The thickness and layering of the sheets were identified by optical microscope, invoking recently reported specific optical color contrast, and further confirmed by AFM and Raman spectroscopy. The MoS2 transistors with different thicknesses were assessed for gas-sensing performances with exposure to NO2, NH3, and humidity in different conditions such as gate bias and light Irradiation. The results show that, compared to the single-layer counterpart, transistors of few MoS2 layers exhibit excellent sensitivity, recovery, and ability to be manipulated by gate bias and green light. Further, our ab initio DFT calculations on single-layer and bilayer MoS2 show that the charge transfer is the reason for the decrease in resistance in the presence of applied field.